ANATOMI DAN KANDUNGAN GIZI TALAS GENDRUK (Colocasia esculenta (L.) Schott) DAN TALAS SAFIRA (Colocasia esculenta (L.) Schott var. Antiquorum) - , CINTYA KUSUMA ADYUTA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Indonesia is a tropical agricultural country. Rice is the primary food and wheat is suplementary food. The demand of primary food production increases according to the increase in population Indonesia. In an effort to national food security, it is necessary to develop alternative food should be done by food diversification. Tuber flour has potential to substitute rice flour consumption. Talas is a one of monocot plant tubers class. Such type of taro in Indonesia are safira taro and gendruk taro. The purpose of this study was to determine differences anatomical characters of safira and gendruk taro and also differences nutrition content of taro flour. Anatomical characters of safira and gendruk taro were qualitatively analysis as a descriptive. Anatomical characters of safira and gendruk taro were prepared by embedding and non-embedding method. Nutrition content of taro flour were quantitively measured by proximate and calori analysis. The results showed there were differences between anatomical characters of safira and gendruk taro. Calcium oxalate crystals present in the stem of safira taro and tuber of gendruk taro. The results of analysis nutrition content showed there were significant differences in the levels of ash, protein, and carbohydrates of the two varieties taro flour. Safira taro flour have water content (3,21%), ash (6,156%), fat (0,848%), protein (6,076%), and carbohydrate (83,71%). Gendruk taro flour have water content (3,72%), ash (4,28%), fat (0,756%), protein (3,422%), and carbohydrate (87,822%). Safira and gendruk taro flour gendruk have a higher carbohydrate than belitung taro flour, rice flour, and wheat flour. Both taro flour is a source of carbohydrates that can substitute consumption of rice or wheat.